Diet of Philodryas olfersii (Serpentes, Colubridae) during hydroelectric dam flooding in southern Brazil - Leite, Pedro Terra; Kaefer, Igor L.; Cechin, Sônia Zanini (North-Western Journal of Zoology, 2009)
We describe aspects of the feeding ecology of a population of the colubrid snake Philodryas olfersii in central Rio Grande do Sul State, Brazil. Based on specimens obtained during the fauna rescue operation of Dona Francisca hydroelectric powerplant, we conducted the first analysis of the diet of a snake during artificial flooding of an area in Brazil. Females attained larger body sizes than males, and ingested heavier prey. We observed a high proportion of recently-fed individuals; mammals were the most frequent prey, followed by birds and frogs. Our results differ drastically from those obtained for P. olfersii in adjacent areas. The frequency of items and dominance of major prey categories in the diet of this snake seem to have been influenced by an unusual exposure of rodents and, consequently, changes in prey detectability resulting from the dam flooding. © NwjZ, Oradea, Romania, 2009.
Keywords: Anura; Aves; Colubridae; Mammalia; Philodryas; Philodryas Olfersii; Rodentia; Serpentes